PATH LOSS ESTIMATION ON SUB 6 GHZ AND MILLIMETER WAVE FREQUENCY USING FINE-TUNING - Arifiansyah Brahma B, Muhammad
One of the important factors that affect the performance of a wireless network is the received power level which is determined by several parameters. One of these parameters is path loss whose value is random with a large deviation, even though it is measured at the same distance from the transmitter. In fact, an accurate path loss value is crucial in wireless communication network planning. The determination of the path loss value based on the empirical model has considered